Speech Therapists Roles in Multisectoral Collaboration for Children with Special Needs: A Case Study in Indonesian Special Schools - Dian Atnantomi Wiliyanto; Rizki Husadani; Sinar Perdana Putra (Department of Special Education, 2025)
To improve their communication skills, children with special needs (CSN) need a system that combines education and therapy, including speech therapy. This study aims to outline the role of speech therapists in working with teachers, parents, healthcare professionals, and others in special schools. We used a case study design and a mixed-methods approach for the research. The study involved 54 participants. We collected data through an online survey created with Google Forms. The survey results show that speech therapists in schools have six key roles: identifying and assessing needs, planning programs together, implementing integrated interventions, communicating and coordinating efforts, evaluating progress, and advocating for students. The advocacy role scored the highest, with an average of 4.50 (SD = 0.50), which is considered very high. The descriptive data also highlighted other challenges, including a lack of proper infrastructure and materials, poor coordination among different sectors, and limited government support for including speech therapy in schools.